Haksız rekabet hukukunda sözleşmeyi ihlale veya sona erdirmeye yöneltme - Sarıkaya, Sinan (My University, 2014)
Piyasalarda gerçekleştirilen kıyasıya rekabet, halihazırda sözleşme ilişkisi içerisinde bulunan piyasa katılımcılarını mevcut sözleşmelerini ihlal ederek daha avantajlı sözleşmeler yapmaya itebilmektedir. Her ne kadar bir kişinin sözleşmesini ihlal etme ve bir başkası ile sözleşme yapma özgürlüğü bulunsa da; sözleşenleri sözleşmelerini ihlale yöneltme, ticari ahlak ve dürüstlük kurallarına ters düşer. Nitekim ticari ahlak, her piyasa aktörünün müşteri veya çalışan bulmak için dürüst bir rekabete girişeceği ve rakiplerin müşteri veya işçilerini ayartmayacağı anlayışını esas alır. Bu çalışmada sözleşmeyi ihlale veya sona erdirmeye yöneltme fiilinin haksız rekabet hukukundaki görünümleri ele alınmaktadır. TTK.55/ I-b’de dört bent halinde yapılan düzenleme, sözleşmeyi ihlale yahut sona erdirmeye yöneltme fiillerini haksız rekabet sayarak, Türk hukukuna yeni bir boyut kazandırmıştır. Bunun yanında, herhangi bir sebeple özel hükümler kapsamında değerlendirilemeyen sözleşmeyi ihlale veya sona erdirmeye yöneltme fiillerinin, TTK.54’te yer alan genel hüküm sayesinde haksız rekabet teşkil etmesi mümkündür. zleşmeyi ihlale yöneltme, sözleşmeyi sona erdirmeye yöneltme, müşteri veya çalışan ayartma, haksız rekabet.

Fierce competition in the markets may prompt the market participants, who are already engaged in contractual relations, to enter into more advantageous agreements by breaching their existing contracts. Although each person is free to violate a contract and enter into a new one with another party, inciting a contracting party to breach its contact is against the principles of morals and good faith. Hence, the business ethics is based on the principle that each market participant will enter into fair competition in order to find customers and employees and will not incite the costumers or employees of its competitors. This study deals with the aspects of the act of inciting the breach or termination of a contract in the unfair competition law. The first part focuses on the historical background of the act and its place amongst the comparative law and the Turkish law. The study proceeds with a detailed examination of Article 5/ I-b of the Turkish Commercial Code by means of separate analysis of each sub-paragraphs of this article, which, by assuming the acts of inciting the breach or termination of a contract as unfair competition, brought a new dimension to the Turkish law. Thus, all the acts of inciting the breach or termination of a contract with whichever motive, which are not within the scope of the special provisions of Article 55, may be considered as unfair competition by virtue of the general provision set forth under Article 54 of the Turkish Commercial Code. The last part deals with the conditions of the foregoing and the most common examples that may be encountered. Inducement breach of contract, inducement termination of contract, seducing customers or employees, unfair competition
Keywords: Hukuk; Rekabet; Sözleşme